Ten new insights in climate science 2021: a horizon scan. (18th October 2021) - Martin, Maria A.; Sendra, Olga Alcaraz; Bastos, Ana; Bauer, Nico; Bertram, Christoph; Blenckner, Thorsten; Bowen, Kathryn; Brando, Paulo M.; Rudolph, Tanya Brodie; Büchs, Milena; Bustamante, Mercedes; Chen, Deliang; et al.
Abstract : Non-technical summary: We summarize some of the past year's most important findings within climate change-related research. New research has improved our understanding about the remaining options to achieve the Paris Agreement goals, through overcoming political barriers to carbon pricing, taking into account non-CO2 factors, a well-designed implementation of demand-side and nature-based solutions, resilience building of ecosystems and the recognition that climate change mitigation costs can be justified by benefits to the health of humans and nature alone. We consider new insights about what to expect if we fail to include a new dimension of fire extremes and the prospect of cascading climate tipping elements. Technical summary: A synthesis is made of 10 topics within climate research, where there have been significant advances since January 2020. The insights are based on input from an international open call with broad disciplinary scope. Findings include: (1) the options to still keep global warming below 1.5 °C; (2) the impact of non-CO2 factors in global warming; (3) a new dimension of fire extremes forced by climate change; (4) the increasing pressure on interconnected climate tipping elements; (5) the dimensions of climate justice; (6) political challenges impeding the effectiveness of carbon pricing; (7) demand-side solutions as vehicles of climate mitigation; (8) the potentials and caveats of nature-based solutions; (9) how building resilience of marine ecosystems is possible; and (10) that the costs of climate change mitigation policies can be more than justified by the benefits to the health of humans and nature. Social media summary: How do we limit global warming to 1.5 °C and why is it crucial? See highlights of latest climate science.